Making stillbirths visible: a systematic review of globally reported causes of stillbirth. (29th November 2017) - Reinebrant, HE; Leisher, SH; Coory, M; Henry, S; Wojcieszek, AM; Gardener, G; Lourie, R; Ellwood, D; Teoh, Z; Allanson, E; Blencowe, H; Draper, ES; et al.
Abstract : Background: Stillbirth is a global health problem. The World Health Organization (WHO) application of the International Classification of Diseases for perinatal mortality (ICD‐PM) aims to improve data on stillbirth to enable prevention. Objectives: To identify globally reported causes of stillbirth, classification systems, and alignment with the ICD‐PM. Search strategy: We searched CINAHL, EMBASE, Medline, Global Health, and Pubmed from 2009 to 2016. Selection criteria: Reports of stillbirth causes in unselective cohorts. Data collection and analysis: Pooled estimates of causes were derived for country representative reports. Systems and causes were assessed for alignment with the ICD‐PM. Data are presented by income setting (low, middle, and high income countries; LIC, MIC, HIC). Main results: Eighty‐five reports from 50 countries (489 089 stillbirths) were included. The most frequent categories were Unexplained, Antepartum haemorrhage, and Other (all settings); Infection and Hypoxic peripartum (LIC), and Placental (MIC, HIC). Overall report quality was low. Only one classification system fully aligned with ICD‐PM. All stillbirth causes mapped to ICD‐PM. In a subset from HIC, mapping obscured major causes. Conclusions: There is a paucity of quality information on causes of stillbirth globally. Improving investigation of stillbirths and standardisation of audit and classification is urgently needed and should be achievable in all well‐resourced settings. Implementation of the WHO Perinatal Mortality Audit and Review guide is needed, particularly across high burden settings. Funding: HR, SH, SHL, and AW were supported by an NHMRC‐CRE grant (APP1116640). VF was funded by an NHMRC‐CDF (APP1123611). Tweetable abstract: Urgent need to improve data on causes of stillbirths across all settings to meet global targets. Plain Language Summary: Background and methods: Nearly three million babies are stillborn every year. These deaths have deep and long‐lasting effects on parents, healthcare providers, and the society. One of the major challenges to preventing stillbirths is the lack of information about why they happen. In this study, we collected reports on the causes of stillbirth from high‐, middle‐, and low‐income countries to: (1) Understand the causes of stillbirth, and (2) Understand how to improve reporting of stillbirths. Findings: We found 85 reports from 50 different countries. The information available from the reports was inconsistent and often of poor quality, so it was hard to get a clear picture about what are the causes of stillbirth across the world. Many different definitions of stillbirth were used. There was also wide variation in what investigations of the mother and baby were undertaken to identify the cause of stillbirth. Stillbirths in all income settings (low‐, middle‐, and high‐income countries) were most frequently reported as Unexplained, Other, and Haemorrhage (bleeding) . Unexplained and Other are not helpful in understanding why a baby was stillborn. In low‐income countries, stillbirths were often attributed to Infection and Complications during labour and birth . In middle‐ and high‐income countries, stillbirths were often reported as Placental complications . Limitations: We may have missed some reports as searches were carried out in English only. The available reports were of poor quality. Implications: Many countries, particularly those where the majority of stillbirths occur, do not report any information about these deaths. Where there are reports, the quality is often poor. It is important to improve the investigation and reporting of stillbirth using a standardised system so that policy makers and healthcare workers can develop effective stillbirth prevention programs. All stillbirths should be investigated and reported in line with the World Health Organization standards. Abstract : Tweetable abstract Urgent need to improve data on causes of stillbirths across all settings to meet global targets.